Attention Effects of Mindfulness-Based Cognitive Therapy in Formerly Depressed Patients. Issue 4 (December 2014) - Verhoeven, Josine E.; Vrijsen, Janna N.; van Oostrom, Iris; Speckens, Anne E. M.; Rinck, Mike
Mindfulness-based cognitive therapy (MBCT) is a group intervention designed to prevent relapse in recurrently depressed patients. It is not clear which cognitive processes accompany MBCT's clinical effects. This study examined effects of MBCT on attentional processes in remitted depressed patients in order to further identify the mechanisms of change in MBCT. Remitted depressed patients (N = 28) completed both subjective and objective measures of attention before and after participation in MBCT. The MBCT group was compared to a control group of remitted depressed patients not participating in MBCT (N = 26). While MBCT did not show effects on subjective measures of attention control or on sustained attention, the intervention did appear to be associated with less distraction by task-irrelevant stimuli, particularly negative stimuli. Our findings suggest that MBCT may decrease vulnerability to depression-related environmental cues and thereby decrease the risk of a relapse or recurrence of depression.